2015
DOI: 10.1071/is14025
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny and biogeography of the mite harvestmen (Arachnida : Opiliones : Cyphophthalmi) of Queensland, Australia, with a description of six new species from the rainforests of the Wet Tropics

Abstract: The Wet Tropics of Queensland, Australia, represent the largest remaining fragment of vast rainforests that once covered the entire continent. Over the past few decades the Wet Tropics bioregion has received much attention from biologists interested in the effect of climate change on diversity and distribution of rainforest animals. However, most such studies have focused on vertebrates, and despite considerable interest in the biota of the area, the diversity of many of Wet Tropics invertebrate taxa remains p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(43 citation statements)
references
References 62 publications
2
41
0
Order By: Relevance
“…Details of key anatomical characters and SEM methodology followed Boyer et al . (). Collections of female and juvenile mite harvestmen are not identifiable to species as only males bear species‐specific morphological characters.…”
Section: Methodsmentioning
confidence: 94%
See 3 more Smart Citations
“…Details of key anatomical characters and SEM methodology followed Boyer et al . (). Collections of female and juvenile mite harvestmen are not identifiable to species as only males bear species‐specific morphological characters.…”
Section: Methodsmentioning
confidence: 94%
“…c . 95%) of the Austropurcellia species in the Wet Tropics (Boyer et al ., ; Popkin‐Hall & Boyer, ; Boyer & Reuter, , and one manuscript currently submitted). Consultation with Queensland entomologist Geoff Monteith, who led QM leaf‐litter arthropod surveys for multiple decades and continues to serve as the focal contact for entomologists visiting Northern Queensland, has bolstered our confidence that our current survey does not exclude significant areas that might include unknown diversity, and that it accurately represents the relative diversity of subregions.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous molecular phylogenetic studies on harvestmen with these biological characteristics have shown compelling biogeographic patterns (e.g., Boyer et al 2007, Thomas and Hedin 2008, Giribet et al 2011, Schönhofer et al 2015, Boyer et al 2015). The Travunioidea have a temperate Laurasian distribution with species found in eastern Asia, eastern and western North America, and central Europe, with notable absences from central Asia (Figure 2).…”
Section: Discussionmentioning
confidence: 99%